2017
DOI: 10.4322/0104-4931.ctoar0773
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento De Manual Para Orientações Básicas Do Dia a Dia Para Pessoas Com Esclerose Múltipla

Abstract: Resumo: Objetivo: O estudo visa apresentar as etapas desenvolvidas para o aprimoramento de manual de orientação e sua aplicação com pessoas com esclerose múltipla (EM), ocorrida em um grupo terapêutico conduzido pela Terapia Ocupacional. Conforme as políticas de saúde, a produção de materiais educativos tem caráter multidisciplinar e é útil como ferramenta para a promoção de saúde devido à sua capacidade de aumentar o conhecimento e de solucionar problemas. O caráter crônico e progressivo da EM traz alterações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
6
0
5
Order By: Relevance
“…The use of educational materials contribute to the work team, as a way to reinforce information and counseling developed in an oral way and it serves as a guide in situations of doubts from the user. 18 Even if the process of counseling of caretaker presents a total use, still new situations can emerge and, then new instructions will be needed. This requires clear flows to be envisaged foreseeing such situations, such as a telephone.…”
Section: Children With Health Needs In Home Carementioning
confidence: 99%
“…The use of educational materials contribute to the work team, as a way to reinforce information and counseling developed in an oral way and it serves as a guide in situations of doubts from the user. 18 Even if the process of counseling of caretaker presents a total use, still new situations can emerge and, then new instructions will be needed. This requires clear flows to be envisaged foreseeing such situations, such as a telephone.…”
Section: Children With Health Needs In Home Carementioning
confidence: 99%
“…The use of educational materials, which favor the teaching-learning process, is a practical resource that contributes to complement therapeutic strategies, facilitates understanding, reinforces information and guidance of the MT, and serves as a guide in situations of doubts to users and their caregivers/family members (Pimentel & Toldrá, 2017). Next, the use of this resource is identified: Thus, the use of educational materials is shown as a strategy that strongly contributes to the promotion of health, autonomy and co-responsibility of the users in their care, besides assisting in the search for alternatives to improve health (Brasil, 2004).…”
Section: -Strategies For Health Management and Maintenancementioning
confidence: 99%
“…The fourth category of Group Intervention (BROWN et al, 2016;TOLDRÁ, 2017aTOLDRÁ, , 2017b showed the importance of group development as a space for sharing experiences, helping and expanding the social network support, and the specific benefits pointed out by each of the authors.…”
Section: Vocational Rehabilitationmentioning
confidence: 99%
“…Occupational therapy sessions included: instruction on modified self-care strategies to promote independence and security; guidance and guided practice in the use of adaptive equipment; education on energy conservation strategies; memory training to support ADL and IADL; emotional regulation strategies; and creating a home exercise program for physical activity. Client-centered occupational therapy interventions using occupational-focused evidence have proven effective increasing performance and satisfaction levels in the occupations identified as most important by the patient and the therapist (PREISSNER;ARBESMAN;LIEBERMAN, 2016). Eyssen et al (2013Eyssen et al ( , 2014 described an experimental occupational therapy intervention in eight action steps that guide the Client-centered therapeutic process: (1) first contact between the patient and therapist, with collaborative decisions for the therapy;…”
Section: Vocational Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation